2012
DOI: 10.1128/jb.06161-11
|View full text |Cite
|
Sign up to set email alerts
|

In the NadR Regulon, Adhesins and Diverse Meningococcal Functions Are Regulated in Response to Signals in Human Saliva

Abstract: The Neisseria meningitidis regulator NadR was shown to repress expression of the NadA adhesin and play a major role in NadA phase-variable expression. In this study, we identified through microarray analysis over 30 genes coregulated with nadA in the NadR mutant and defined members of the NadR regulon through in vitro DNA-binding assays. Two distinct types of promoter architectures (I and II) were identified for NadR targets, differing in both the number and position of NadR-binding sites. All NadR-regulated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…The N. meningitidis strains used in this study are listed in Table 1 and include the respective NadR null mutant derivatives, which have been described elsewhere (23). The NGP165 NHBA null mutant was generated as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N. meningitidis strains used in this study are listed in Table 1 and include the respective NadR null mutant derivatives, which have been described elsewhere (23). The NGP165 NHBA null mutant was generated as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…4-HPA is a catabolite of aromatic amino acids and is commonly found in human saliva (22). It has also been recently reported that human saliva itself can induce NadA expression as well as 4-HPA, suggesting that signals capable of inducing NadA expression, which can be mimicked by 4-HPA in vitro, are present in the oropharyngeal niche of meningococcal colonization (23). Moreover, it has also been demonstrated that sera from children convalescent after meningococcal disease are able to recognize NadA, suggesting that NadA is expressed during invasive human infection to a level which is sufficient to elicit anti-NadA antibodies (24).…”
mentioning
confidence: 99%
“…Further, children recovering from invasive meningococcal disease produce specific antibody responses against this antigen (11). NadA expression is regulated at the transcriptional level by the length variation of a tandem repeat region located in the gene promoter (12,13), with expression regulated by NadR, a repressor molecule (14)(15)(16). Expression can be induced by the use of 4-hydroxyphenyl acetic acid, a small molecule secreted in human saliva, which inhibits NadRdependent repression (14).…”
mentioning
confidence: 99%
“…6). This can have physiologically relevant consequences, since gapA was shown to play a role in adhesion (51) and its expression is controlled by the NadR repressor (20). Furthermore, the acetate kinase gene ackA2, which is involved in the production of acetate from acetyl coenzyme A (acetyl-CoA), was downregulated by glucose (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, about one-half of the genes that are essential for systemic infection encode enzymes that are involved in the metabolism and transport of nutrients (15). In addition, several environmental signals have effects on the transcriptional regulation of N. meningitidis during host infections, as shown for iron (16,17), zinc (18), nitric oxide (19), human saliva (20), and human blood (21,22). Therefore, virulence factors and genes essential for survival need to be regulated tightly and rapidly at the gene expression level in order to respond to the various microenvironments encountered during infection.…”
Section: Importancementioning
confidence: 99%